2007
DOI: 10.1590/s1519-566x2007000500011
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical and ultrastructural evidence of lipid secretion by the silk gland of the sugarcane borer Diatraea saccharalis (Fabricius) (Lepidoptera: Crambidae)

Abstract: Neotropical Entomology 36(5): 707-711 (2007) Evidências Histoquímicas e Ultra-Estruturais de Secreção Lipídica pela Glândula da Seda da Broca da Canade-Açúcar, Diatraea saccharalis (Fabricius) (Lepidoptera: Crambidae)RESUMO -A glândula da seda de larvas de Lepidoptera é responsável pela produção da seda usada na secreção de seda de insetos, embora a presença desse componente contribua para a resistência da seda secreção da glândula da seda de larvas de Diatraea saccharalis (Fabricius), bem como caracterizar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…Differences among the 3rd-instar larvae may occur because during the 5th instar of larval development, the silk gland is highly active synthetizing silk (Victoriano and Gregório, 2002;Victoriano et al, 2007) to weave a cocoon for pupation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences among the 3rd-instar larvae may occur because during the 5th instar of larval development, the silk gland is highly active synthetizing silk (Victoriano and Gregório, 2002;Victoriano et al, 2007) to weave a cocoon for pupation.…”
Section: Discussionmentioning
confidence: 99%
“…In the larval stage, the insect has a pair of silk glands that are responsible for the production of silk, which is fully developed in the last instar of larval development (Victoriano and Gregório, 2002;Victoriano et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The structure of insect silk glands has been well studied in Lepidoptera (Akai 1984), Hymenoptera (Silva-Zacarin 2003, Serrão 2005, Victoriano 2007), and especially Bombyx mori , because its silk has great economic value (Iijimaa 1972, Sasaki and Tashir 1976, Sehnal and Akai 1990). The above studies indicated that the major components of the silk or cocoon secreted by the silk gland were friboin and sericin (Akai 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The above studies indicated that the major components of the silk or cocoon secreted by the silk gland were friboin and sericin (Akai 1984). Victoriano (2007) suggested that the silk produced by Diatraea. saccharalis has minor lipid contents and sericin, and that the lipid makes the cocoon waterproof.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation